Differences in EFL Student’s Simile and Metaphor Comprehension: Influence of Gender and Age - Wardana, I Ketut (Universitas Pendidikan Ganesha, 2024)
English simile and metaphor comprehension by EFL students in Indonesia as an imaginative function plays a crucial role in holistic language learning. Therefore, this study aimed to analyze the level of English simile and metaphor comprehension among university students and analyze whether the figure of speech differs according to gender, age, length of study, and different academic backgrounds. The participants were 124 university students in aged 19 to 22 years. Data were collected using 16 English simile and metaphor success test items. The answers were evaluated by two experts. Descriptive statistics and a sequence of Mann-Whitney U tests were applied. This study revealed that students' conception of English similes and metaphors is low on a broad scale. Participants answered 29.11% of the simile questions correctly, while 60.89% of the participants answered the questions incorrectly. Meanwhile, out of eight questions on English metaphors, 38.31% of the students could answer the questions correctly, but 61.69% of the students could not answer the questions. In addition, it was found that the simile and metaphor comprehension of the participants did not differ according to gender but differed based on age, length of study, and academic background. This study advocates that EFL learners should develop their competence in figurative from a cognitive linguistics perspective.